Análisis correlacional de las plataformas digitales Chequeado y Ecuador-Chequea entorno a la inteligencia artificial - Terranova Ordoñez, Marco David (2023)
Journalism and technology have changed the way of interacting with the user; however, for this to happen, professionals in the field have had to adapt to the digital age of the 21st century and with it, to the demands of a society immersed in digital. Within this framework, a phenomenon is born due to misinformation, which, aided by technological immediacy, is disseminated on a large scale through social networks, causing confusion in the verisimilitude of the information, in view of this, Fact-Checking It arises as a methodological response to this phenomenon, since digital journalism has taken another turn of work within digital environments. The present correlational study uses a quantitative and qualitative approach, in addition to using the techniques of content analysis, non-participant observation and interview for data collection. From this, 3 verified contents related to Artificial Intelligence were used within the Instagram platforms of the digital media Chequeado and Ecuador-Chequea. This research shows how the Fact-Checking methodology is applicable for the verification of disinformation content, likewise, it shows the filters and processes that each medium uses to interact with the audience. It should be noted that the categories and qualifications that each medium grants are subject to misinformation content and false news, since there is a difference between these two categories and it is what has set the course in digital journalistic work